Managing corporate social responsibility : a communication approach - Coombs, W. Timothy; Holladay, Sherry J. (Malden, MA : Wiley-Blackwell, 2012)
'Managing Corporate Social Responsibility offers a strategic, communication-centred approach to integrating CSR into organizations. Drawing from a variety of disciplines and written in a highly accessible style, the book guides readers in a focused progression providing the key points they need to successfully navigate the benefits and implications of managing CSR. Chapters are organized around a process model for CSR that outlines steps for researching, developing, implementing, and evaluating CSR initiatives Emphasizes stakeholder engagement as a foundation throughout the CSR Process Model Discusses ways to maximize the use of social media and traditional media throughout the process Offers international examples drawn from a variety of industries including: The Forest Stewardship Council, Starbucks Coffee, and IKEA. Draws upon theories grounded in various disciplines, including public relations, marketing, media, communication, and business '--
'Corporate Social Responsibility (CSR) has become central to many businesses as they negotiate in an increasingly global marketplace. This book offers a strategic, communication-centred approach to integrating CSR into organizations, founded in stakeholder engagement and dialogue. It is structured around the CSR Process Model, which guides readers through the research, development, implementation, and evaluation of CSR initiatives. Corporate reputations are increasingly dependent upon CSR, which in turn signals the importance of this topic for organizational success and the need to integrate stakeholders into this process. Lively, international examples are used throughout and are drawn from a variety of industries to illustrate the challenges of doing CSR well. Topics covered include maximizing the use of social media and traditional media; creating strategic initiatives that reflect the organization's missions and its capabilities; communicating to promote CSR efforts; collaborating with third party organizations; assessing internal and external stakeholder expectations and involving stakeholders in CSR efforts; and managing challenges to an organization's CSR record. This highly accessible book draws from a variety of disciplines to illustrate how corporate social responsibility should be viewed as an ongoing process grounded in effective communication practices'--
Includes bibliographical references and index.
Keywords: Social responsibility of business; Business communication